Membrane expression and significance of TRAIL death receptors DR4 and DR5 in Pancreatic cancer (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Tumor necrosis factor related-apoptosis-inducing ligand (TRAIL) is a powerful and selective activator of apoptosis in many cancer cells. We aim to investigate the expression and significance of TRAIL death receptor DR4 and DR5 in pancreatic cancer (PC) tissues.Method: Twenty-eight histologically verified samples of PC tissue were collected between 2018 and 2019. TRAIL death receptor expression profiles were determined by immunohistochemistry.Result: Death receptor DR4 and DR5 were expressed in the PC tissue and the adjacent non-cancerous pancreatic tissues, the expression of DR4 and DR5 in the PC tissue was significantly higher than that of the adjacent non-cancerous pancreatic tissues (p